La selección del inmigrante “apto”: leyes migratorias de inclusión y exclusión en Colombia (1920-1937) - Iván Olaya (Centre de Recherches sur les Mondes Américains, 2018)
Between 1920 and 1937, the Colombian government decreed a number of immigration laws aiming at protecting the country from the entrance of “undesirable elements” who could jeopardise the population’s health and degenerate its “genetic background”. Even if the Colombian immigration laws had already referred to the “white” immigrant as the “fit” one to “civilise” the country in the XIX century, this racialisation was set in biological and hereditary terms in the 1920s and 1930s on account of scientific currents which supported the racial discourse. Colombia issued restrictive immigration laws in light of its national social and economic context as well as international tendencies and scientific currents during this period.